The role of virtual classrooms in improving the educational process from the point of view of private school teachers for the primary stage in Jeddah Governorate - Al-Harbi, Abrar Salem (Journal of Curriculum and Teaching Methodology, 2023)
This study aimed to investigate the role of virtual classrooms in improving the educational process from the point of view of female teachers in private schools for the primary stage in Jeddah Governorate. The research used a descriptive approach, where the study population consisted of female teachers in private schools for the primary stage in Jeddah Governorate, which numbered 1,235 female teachers. A sample was taken. Of them, approximately 5% represented 60 female teachers. The questionnaire was used as a tool for the study, and the study reached agreement on the role of virtual classrooms in improving the educational process from the point of view of female teachers in private schools for the primary stage. We find that the phrase (virtual classrooms help female teachers develop courses on... The method of organizing content) was the most agreed upon statement by the respondents, at a rate of 78.3%. The respondents also strongly agreed that virtual classes help teachers pass messages between participants to conduct discussions between them via the Internet, at a rate of 53.3%, and recommended The study has a set of recommendations, the most important of which is implementing virtual classrooms in all schools, whether governmental or private, with the aim of benefiting from its positive results and effects. The researcher also recommends implementing the study on the same sample using the type of evaluative study. The researcher also recommended the possibility of implementing a future study with the same goal, but on another sample, such as female teachers. In public schools.